If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*x)/4 = 9/2 // - 9/2
(3*x)/4-(9/2) = 0
(3*x)/4-9/2 = 0
3/4*x-9/2 = 0 // + 9/2
3/4*x = 9/2 // : 3/4
x = 9/2/3/4
x = 6
x = 6
| 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= | | -12=-3/4z | | 17q-14xq=11q | | 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 | | 3x(12-3)=27 | | 6x+19=8x+7 | | -2(5x-6)-12=-2(9s+4)-3 | | b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) | | 180=6000*.12*t | | 4(5x-1)-4=14x-2 | | 5(3x+1)=2(5x-4)+6x | | 27(1.4+1.2)-26(1.4+1.2)= | | -65.375=7.2(9c+1) | | (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) |